Heaving force of frozen ground. I. Mainly on the results of field researches - Kinoshita, S.; Ono, T.; National Research Council of Canada. Division of Building Research (National Research Council of Canada, 1966)
The force exerted on an object on the ground or buried in the ground is the heaving force due to freezing. The smaller the extent of heaving permitted the greater the heaving force. The maximum force when no heaving is permitted can be divided into two components, the basal heaving force and the adfreezing force. Field apparatus was constructed to measure the uplift force and after one winter' s operation the results are as follows for a soil consisting of about 15% clay size and 20% silt size and the remained sand. The greatest depth of freezing was 57 cm; the basal heaving force was 29.3 kg/cm[2], and the maximum adfreezing force was 2.1 kg/cm[2] in an iron pipe, 1.65 kg/cm[2] in a vinyl pipe, 1.16 kg/cm[2] in a concrete pipe and 0.52 kg/cm[ 2] in a concrete pipe coated with a furan resin paint. Although the depth of freezing did not decrease during the winter, the heaving forces underwent increases and decreases several times. It is believed that the decrease of heaving force was due to the relief of stress as a result of cessation of heaving of the ground. The authors intend to continue the field work and to initiate laboratory experiments in order to finish this project. La force qui s'exerce sur un oblet qui se trouve sur le sol ou enfoui dans le sol est La force de soulèvement due au gel. Plus l'espace disponible est restreint, plus La force de soulèvement est grande. La force maximale, lorsqu'il n'y a pas d'espace pour permettre le soulèvement, peut se diviser en deux composantes: La force de soulèvement basale et La force de congélation adhérente. On a concu un appareil pour mesurer La force de soulèvement sur le terrain. Bien que la profondeur de gel n'ait pas diminué au cours de l'hiver, les forces de soulèvement ont augmenté et diminué plusieurs fois. Il semble que la force de soulè vement ait diminué par suite du relâchement de la contrainte dû à l'interruption du soulèvement du sol. Peer reviewed: No NRC publication: Yes